Pembelajaran Matematika Menggunakan Model Learning Cycle 5E Untuk Meningkatkan Kemampuan Penalaran Matematis Siswa SMP 30 Padang - Pitriati, Pitriati (Indonesian Journal of Science and Mathematics Education, 2019)
Abstract: This research is motivated by the low activity and competitiveness of students in working on mathematical questions and the lack of reasoning abilities of students in carrying out the tasks given. The purpose of this study is to examine the improvement of reasoning abilities of students who have learned the Learning Cycle 5e model. Learning Cycle is a conceptual framework that is used as a guide in conducting student-centered learning processes. This type of research is classroom action research conducted collaborating between researchers and mathematics teachers. The subjects in this study were class IX.1 SMPN 30 Padang in the 2017/2017 academic year, totaling 32 people. The data method used in this study is observation, field notes and documentation. Data analysis techniques were carried out in qualitative and quantitative descriptive. The results of this class action research showed an increase in student activity so that there was an increase in mathematical reasoning abilities of students far increased compared to students in learning that were not given Learning Cycle 5e.Abstrak: Penelitian ini dilatarbelakangi oleh rendahnya aktivitas dan daya saing siswa dalam mengerjakan soal-soal matematika serta kurangnya kemampuan penalaran siswa dalam mengerjakan tugas-tugas yang diberikan. Tujuan penelitian ini untuk menelaah peningkatan kemampuan penalaran siswa yang memperoleh pembelajaran model Learning Cycle 5e. Learning Cycle adalah suatu kerangka konseptual yang digunakan sebagai pedoman dalam melakukan proses pembelajaran yang terpusat pada siswa. Jenis penelitian ini adalah penelitian tidakan kelas yang dilakukan kolaburasi antara peneliti dengan guru matematika. Subjek dalam penelitian ini adalah siswa kelas IX.1 SMPN 30 Padang tahun pelajaran 2017/2017 yang berjumlah 32 orang. Metode data yang digunakan pada penelitian ini adalah observasi, catatan lapangan dan dokumentasi. Teknik analisis data dilakukan secara deskriptif kualitatif dan kuantitatif. Hasil penelitian tindakan kelas ini menunjukan peningkatan keaktifan siswa sehingga terjadi peningkatan kemampuan penalaran matematis siswa jauh meningkat dibandingkan dengan siswa pada pembelajaran yang tidak diberikan Learning Cycle 5e.